2021
DOI: 10.1002/tox.23293
|View full text |Cite
|
Sign up to set email alerts
|

Glyburide attenuates B(a)p and LPS‐induced inflammation‐related lung tumorigenesis in mice

Abstract: Glyburide (Gly) could inhibit NLRP3 inflammasome, as well as could be treated with Type 2 diabetes as a common medication. Despite more and more studies show that Gly could influence cancer risk and tumor growth, it remains unclear about the effect of Gly in lung tumorigenesis. To evaluate whether Gly inhibited lung tumorigenesis and explore the possible mechanisms, a benzo(a)pyrene [B(a)p] plus lipopolysaccharide (LPS)-induced non-diabetes mice model was established with B(a)p for 4 weeks and once a week (1 m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
(78 reference statements)
0
9
0
Order By: Relevance
“…In laboratory studies, glibenclamide was reported to show contradictory influences on cancer development by interacting with the ATP-sensitive potassium channels, e.g. , sulfonylurea receptor 1, peptide transporter 1, and AKR1Cs, and to attenuate the inflammation-related tumorigenesis by inhibiting NLRP3 inflammasome . Diltiazem has been reported to enhance antitumor effects of multiple chemotherapeutics (gemcitabine, 5-fluorouracil, docetaxel, vincristine, and bortezomib) through various mechanisms including reducing drug resistance, upregulating autophagy and apoptosis-related signal pathways, and inhibition of P-glycoprotein. Thus far, the direct antitumor or antimetastatic effect of diltiazem or glibenclamide has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In laboratory studies, glibenclamide was reported to show contradictory influences on cancer development by interacting with the ATP-sensitive potassium channels, e.g. , sulfonylurea receptor 1, peptide transporter 1, and AKR1Cs, and to attenuate the inflammation-related tumorigenesis by inhibiting NLRP3 inflammasome . Diltiazem has been reported to enhance antitumor effects of multiple chemotherapeutics (gemcitabine, 5-fluorouracil, docetaxel, vincristine, and bortezomib) through various mechanisms including reducing drug resistance, upregulating autophagy and apoptosis-related signal pathways, and inhibition of P-glycoprotein. Thus far, the direct antitumor or antimetastatic effect of diltiazem or glibenclamide has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The glyburide may be beneficial to the anti-cancer effect by regulating ATP-binding cassette protein super-family and ATP-sensitive potassium channels [104] . A recent non-diabetes mice model study suggested that glyburide might inhibit NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome to attenuate inflammation-related lung tumorigenesis [105] . Another case study showed that gliclazide tended to have a decreased risk of liver cancer [101] .…”
Section: Repositioning Potential Of Antidiabetic Drugsmentioning
confidence: 99%
“…As a result of the inflammatory response caused by LPS, pro‐inflammatory cytokines released and further generated the reactive oxygen species (ROS), which leading the induction of oxidative stress 14 . When LPS activates the host receptor toll‐Like Receptor 4 (TLR‐4), it can further trigger the release of inflammatory mediators 15 . LPS activates the TLR‐4 receptor, which further triggers the upregulation of several pathways including the activation of mitogen‐activated protein kinases (MAPKs), nuclear transcription factor κ B (NF‐κB) and NLR family pyrin domain containing 3 (NLRP3) inflammasome 12,16 .…”
Section: Introductionmentioning
confidence: 99%
“…14 When LPS activates the host receptor toll-Like Receptor 4 (TLR-4), it can further trigger the release of inflammatory mediators. 15 LPS activates the TLR-4 receptor, which further triggers the upregulation of several pathways including the activation of mitogenactivated protein kinases (MAPKs), nuclear transcription factor κ B (NF-κB) and NLR family pyrin domain containing 3 (NLRP3) inflammasome. 12,16 LPS is a powerful trigger for the release of several proinflammatory cytokines, which are involved in the development of ALI.…”
Section: Introductionmentioning
confidence: 99%